The Effect of Centric Steel Braced Frames with High Ductility Level on the Performance of Steel Structures - Ülker, Mustafa; Işık, Ercan; Ülker, Mehmet (Fırat University, 2018)
The basic functions expected from any structure are generally sufficient rigidity, ductility and stiffness. In this study, the effect of steel ducts with high ductility level on the performance of steel structures was investigated. For this purpose, calculations were made using five different types of central steel curtains for steel flues of any hospital building. Period, frequency, modal addition rates, displacement and rotation values are calculated and compared for each different central steel screen. The aim of the study is to be informed about the central steel slabs with high ductility level and to have information about which of the most suitable central steel slabs will be chosen.
Keywords: Engineering; Mühendislik